What Is the Best Way for Patients to Take Photographs of Medical Images (Radiographs, CT, and MRI) Using a Smartphone?. Issue 10 (29th October 2021) - Yang, Xiao-jiang; Wei, Wei; Zhang, Yang; Wang, Ya-nan; Zhang, Nan; Li, Tian-qing; Ma, Tian-cheng; Zhang, Ke-ying; Jiang, Ming-chun; Ma, Zhen-sheng
Abstract: Background: Teleradiology has become one of the most important approaches to virtual clinical diagnosis; its importance has only grown during the coronavirus 2019 pandemic. In developing countries, asking patients to take photographs of their images using a smartphone can facilitate the process and help keep its costs down. However, the images taken by patients with smartphones often are of poor quality, and there is no regulation or standard instruction about how to use smartphones to take photographs of medical examination images effectively. These problems limit the use of smartphones in remote diagnosis and treatment. Questions/purposes: To formulate a set of guidelines for the most appropriate and effective use of smartphones to capture images (radiographs, CT images, and MR images), and to determine whether these guidelines are more effectively adopted by patients of differing ages and genders. Methods: In this prospective study, a set of step-by-step instructions was created with the goal of helping patients take better smartphone photographs of orthopaedic diagnostic images for transfer to telemedicine services. Following the advice of surgeons, experts in smartphone technology, imaging experts, and suggestions from patients, the instructions were modified based on clinical experience and finalized with the goals of simplicity, clarity, and convenience. Potentially eligible patients were older than 18 years, had no cognitive impairment, and used smart phones. Based on that, 256 participants (patients or their relatives and friends) who visited the orthopaedic department of our hospital from June to October 2020 potentially qualified for this study. A total of 11% (29) declined to participate, leaving 89% (227) for analysis here. Their mean age was 36 ± 11 years, 50% were women (113 of 227), and the patient himself/herself represented in 34% (78 of 227) of participants while relatives or friends of patients made up 66% (149 of 227) of the group. In this study, the diagnoses included spinal stenosis (47% [107 of 227]), disc herniation without spinal stenosis (31% [71 of 227]), vertebral fractures (14% [32 of 227]), and other (7% [17 of 227]). Each study participant first took photographs of their original medical images based on their own knowledge of how to use the smartphone camera function; each participant then took pictures of their original images again after receiving our instructional guidance. Three senior spine surgeons (YZ, TQL, TCM) in our hospital analyzed, in a blinded manner, the instructed and uninstructed imaging files based on image clarity (the content of the image is complete, the text information in the image is clearly visible, there is neither reflection nor shadow in the image) and image position (it is not tilted, curled, inverted, or reversed). If either of these conditions was not satisfied, the picture quality was deemed unacceptable; two of three judges' votes determined the outcome. Interobserver reliability with kappa values for the three judges were 0.89 (YZ versus TQL), 0.92 (YZ versus TCM), and 0.90 (TQL versus TCM). Results: In this study, the overall proportion of smartphone medical images deemed satisfactory increased from 40% (91 of 227) for uninstructed participants to 86% (196 of 227) for instructed participants (risk ratio 2.15 [95% CI 1.82 to 2.55]; p<0.001). The proportion of acceptable-quality images in different age groups improved after instruction, except for in patients aged 51 years or older (3 of 17 uninstructed participants versus 8 of 17 instructed participants; RR 2.67 [95% CI 0.85 to 8.37]; p = 0.07). The proportion of acceptable-quality images in both genders improved after instruction, but there was no difference between the genders. Conclusion: We believe our guidelines for patients who wish to take smartphone photographs of their medical images will decrease image transmission cost and facilitate orthopaedic telemedicine consultations. However, it appears that patients older than 50 years are more likely to have difficulty with this approach, and if so, they may benefit from more hands-on assistance from clinic staff or younger relatives or friends. The degree to which our findings are culture-specific should be verified by other studies in other settings, but on the face of it, there is little reason to believe our findings would not generalize to a reasonable degree. Other studies in more heterogeneous populations should also evaluate factors related to levels of educational attainment and wealth differences, but in the meantime, our findings can give clinical teams an idea of which patients may need a little extra assistance. Level of Evidence: Level II, therapeutic study.